UPAYA BP2MI MELINDUNGI PEKERJA MIGRAN PEREMPUAN DALAM KERANGKA GLOBAL COMPACT FOR MIGRATION (GCM) - Nesfiana, Elbi; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The phenomenon of international migration had increased, bringing complex challenges for female migrant workers, especially those deployed through non-procedural channels. They were vulnerable to exploitation and human rights violations. Indonesia, as one of the largest sending countries in Southeast Asia, bore responsibility for protecting its citizens abroad. This study analyzed BP2MI’s efforts to protect female migrant workers within the framework of the Global Compact for Migration (GCM). It employed a descriptive qualitative method using secondary data from official BP2MI documents, government policies, GCM documents related to women’s protection, as well as academic sources and online media. The findings showed that BP2MI had undertaken various strategic measures, including gender-based protection during pre-departure, placement, and post-placement phases, the strengthening of integrated services, and inter-agency coordination. However, field implementation still faced obstacles related to resources and cross-sector coordination. Keywords: BP2MI, women migrant workers, protection, Global Compact for Migration, GCM, migration policy.